Restorative Justice for the Protection of Children in Conflict with the Law: A Legislative Perspective in Muslim Countries in Southeast Asia - Ernawati; Baharudin, Erwan; Moh Shohib; Arianto, Henry (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2026)
Children in conflict with the law represent one of the most vulnerable groups within the criminal justice system because they stand at the intersection of legal accountability and the state’s responsibility to safeguard their rights and best interests. In the development of contemporary criminal law, restorative justice has gained increasing recognition as an alternative paradigm that prioritizes restoration, rehabilitation, and the social reintegration of child offenders, particularly in response to the shortcomings of retributive justice. This reseach examines the substance of restorative justice within the juvenile justice systems of three Muslim-majority Southeast Asian countries, namely Indonesia, Malaysia, and Brunei Darussalam, with particular attention to differences in normative recognition and their implications for the protection of children’s rights. The study employs normative legal research using a comparative law approach, focusing on statutory frameworks and institutional mechanisms governing the rehabilitation of children in conflict with the law in the three jurisdictions. The findings reveal that Indonesia expressly incorporates restorative justice and diversion into its positive legal framework, while Malaysia and Brunei Darussalam recognize similar principles more implicitly through rehabilitative and non-custodial measures. These normative differences affect the consistency of implementation, the degree of legal certainty, and the overall effectiveness of restorative justice practices. Accordingly, regulatory strengthening and policy harmonization among Southeast Asian Muslim countries are essential to promoting a sustainable juvenile justice system that is consistently oriented toward rehabilitation and the best interests of the child.